ACQUISITION OF PARENTING SKILLS FOR INSTITUTIONALIZED PREGNANT ADOLESCENTS - Presado, Maria Helena (2024)
Teenage pregnancy is considered a public health problem, although the fertility rate in this age group has decreased, in Portugal in 2022 there were 6.2 ‰ pregnant teenagers. Some, without family support and in a situation of increased vulnerability; reside in shelter institutions, leading pregnant women to require psychosocial intervention to develop personal and parental skills that are fundamental to fulfilling the role of mother. Social support is essential to protect pregnant women and children, prevent risky behavior and promote the development of parental skills, facilitating the transition process to parenthood. The insufficient number of employees in social and health institutions has a negative impact on the development of their personal, social, professional or parental skills among pregnant teenagers. Objective: understand the process of acquiring parental skills among institutionalized pregnant teenagers. Methods Exploratory, descriptive study with a qualitative approach, using interviews with seven pregnant teenagers living in three shelter institutions. Results: The content analysis of the report of the life experiences of 7 participants reveals fear and insecurity. They consider nurses' support during pregnancy to be important for the acquisition of parental skills through the integration of childbirth and parenting preparation programs. They reveal a lack of postpartum support. Emphasizing that the support of techniques from the host institution is important. Conclusions. Pregnant teenagers need psychosocial support, pregnancy monitoring and postpartum follow-up that is more suited to individual needs. Greater coordination and complementarity between health and social services is imperative.